The Role of Brand Local Image in Mediating the Effect of Brand Experience and Brand Authenticity on Brand Loyalty: A Study on Customers of Modern Outlets of Aming Coffee - Zhakia Putri Amanda (Pascasarjana STIE Amkop Makassar, 2026)
The rapid growth of local coffee shops has intensified competition, requiring differentiation strategies based on brand identity and brand experience to build customer loyalty. This study aims to analyze the effect of brand authenticity and brand experience on brand loyalty, with brand local image as a mediating variable among Aming Coffee customers. This research employs a quantitative approach through an online survey of 230 respondents who have previously made purchases. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that brand authenticity and brand experience have a positive and significant effect on both brand local image and brand loyalty. Furthermore, brand local image significantly mediates the relationship between brand authenticity and brand experience on brand loyalty. These findings suggest that brand authenticity, supported by positive brand experiences and strengthened through a strong local brand image, can enhance long-term customer attachment and loyalty.